2013
DOI: 10.1136/tobaccocontrol-2012-050765
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco display and brand communication at the point of sale: implications for adolescent smoking behaviour

Abstract: BackgroundIn England, point-of-sale (PoS) displays in larger shops were prohibited in April 2012, with an exemption for smaller retailers until 2015. The aim of this study was to examine the association between tobacco displays and brand communication at the PoS and adolescent smoking behaviour, and to assess the potential benefits likely to accrue from this legislation.MethodsSelf-completion questionnaire survey in students aged 11–15 years in March 2011.ResultsThe odds of ever-smoking doubled for those visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 14 publications
1
59
0
2
Order By: Relevance
“…We have previously reported evidence from a cross‐sectional analysis of the 2011 data from this cohort that noticing tobacco PoS displays more frequently when visiting shops was associated with an increased likelihood of being susceptible to smoking 11. These new prospective data demonstrate that after adjustment for the effects of other determinants of smoking behaviours, visiting shops and noticing PoS displays more frequently is associated with an increased likelihood of non‐susceptible never smokers becoming susceptible to smoking, but is not related to the likelihood of becoming an ever smoker.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…We have previously reported evidence from a cross‐sectional analysis of the 2011 data from this cohort that noticing tobacco PoS displays more frequently when visiting shops was associated with an increased likelihood of being susceptible to smoking 11. These new prospective data demonstrate that after adjustment for the effects of other determinants of smoking behaviours, visiting shops and noticing PoS displays more frequently is associated with an increased likelihood of non‐susceptible never smokers becoming susceptible to smoking, but is not related to the likelihood of becoming an ever smoker.…”
Section: Discussionmentioning
confidence: 90%
“…We received questionnaires from 4302 students (approximately 69% of those eligible, based on the total number of students reported by schools to be on their rolls) from the eight schools surveyed in 2012, of whom 3672 were in school years 8–11 and hence potentially also participants in the 2011 survey 11. We were able to link questionnaires from 2011 and 2012 for 2354 (64%) of these, but had to exclude 47 respondents who did not provide data on susceptibility to smoking in both years, and 37 respondents with incompatible primary outcome responses (24 who reported in 2012 that they were non‐susceptible never smokers, having been ever smokers in 2011; and 13 who indicated that they were susceptible never smokers in 2012, having been ever smokers in 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations